Ultrasonographic Percutaneous Anatomy of the Atlanto‐Occipital Region and Indirect Ultrasound‐Guided Cisternal Puncture in the Dog and the Cat. (9th April 2014) - Etienne, A.‐L.; Audigié, F.; Peeters, D.; Gabriel, A.; Busoni, V.
Summary Cisternal puncture in dogs and cats is commonly carried out. This article describes the percutaneous ultrasound anatomy of the cisternal region in the dog and the cat and an indirect technique for ultrasound‐guided cisternal puncture. Ultrasound images obtained ex vivo and in vivo were compared with anatomic sections and used to identify the landmarks for ultrasound‐guided cisternal puncture. The ultrasound‐guided procedure was established in cadavers and then applied in vivo in seven dogs and two cats. The anatomic landmarks for the ultrasound‐guided puncture are the cisterna magna, the spinal cord, the two occipital condyles on transverse images, the external occipital crest and the dorsal arch of the first cervical vertebra on longitudinal images. Using these ultrasound anatomic landmarks, an indirect ultrasound‐guided technique for cisternal puncture is applicable in the dog and the cat.